A Comprehensive Study on Tetraaryltetrabenzoporphyrins - Ruppel, Michael; Lungerich, Dominik; Sturm, Sabrina; Lippert, Rainer; Hampel, Frank; Jux, Norbert (Chemistry - A European Journal, 2020)
Tetraaryltetrabenzoporphyrins (TATBPs) show, due to their optoelectronic properties, rising potential as dyes in various fields of physical and biomedical sciences. However, unlike in the case of porphyrins, the potential structural diversity of TATBPs has been explored only to little extent, owed mainly to synthetic hurdles. Herein, we prepared a comprehensive library of 30 TATBPs and investigated their fundamental properties. We elucidated structural properties by X-ray crystallography and found explanations for physical properties such as solubility. Fundamental electronic aspects were studied by optical spectroscopy as well as by electrochemistry and brought in context to the stability of the molecules. Finally, we were able to develop a universal synthetic protocol, utilizing a readily established isoindole synthon, which gives TATBPs in high yields, regardless of the nature of the used arylaldehyde and without meticulous chromatographic purifications steps. This work serves as point of orientation for scientists, that aim to utilize these molecules in materials, nanotechnological, and biomedical applications.
CRIS-Team WoS Importer:2020-02-18

Cobalt(II), Zinc(II), Iron(III), and Copper(II) Complexes Bearing Positively Charged Quaternary Ammonium Functionalities: Synthesis, Characterization, Electrochemical Behavior, and SOD Activity - Stojičkov, Marko; Sturm, Sabrina; Čobeljić, Božidar; Pevec, Andrej; Jevtović, Mima; Scheitler, Andreas; Radanović, Dušanka; Senft, Laura; Turel, Iztok; Andjelković, Katarina; Miehlich, Matthias; Meyer, Karsten; et al. (European Journal of Inorganic Chemistry, 2020)
We have synthesized and characterized Co(II) (1), Zn(II) (2), Fe(III) (3) and Cu(II) (4) complexes of 2,2'-[2,6-pyridinediylbis(ethylidyne-1-hydrazinyl-2-ylidene)]bis[N,N,N-trimethyl-2-oxoethanaminium] dichloride (H2LCl2) by NMR, IR, and X-Band EPR spectroscopy, respectively, as well as by single-crystal X-ray structural analysis. H2LCl2 belongs to the class of diacetylpyridine bis(hydrazone) ligands and bears two positively charged quaternary ammonium functionalities. The complexes 1–3 possess a pentagonal-bipyramidal geometry, whereas 4 has square-pyramidal geometry. Redox reactivity and SOD activity of the complexes was studied by means of electrochemical measurements in aqueous-buffer and DMF or DMSO solutions, respectively, as well as by stopped-flow measurements. Complexes 1–3 do not have SOD activity, whereas 4 exhibits a high catalytic rate constant for the superoxide dismutation, kcat = 1.73 × 107 m–1 s–1 (in MOPS buffer solution of pH = 7.4). The results were discussed in terms of complex redox potentials, electrostatic interactions and their spatial distribution, kinetic lability of metal centers, and stability of peroxo intermediates, respectively.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Cobalt; Copper; Electrochemistry; Iron; SOD activity; Structure elucidation